Perceptions of Women in Turkey on the Concepts of “Caesarean Section” and “Vaginal Birth After Caesarean Section”: A Metaphor Analysis - Bıdık, Nazlı Ünlü; Turfan, Esin Çeber (Bangladesh Journal of Medical Science, 2024)
Background Determining how women make sense of their birth preferences with metaphor analysis will be an important step in determining perceptions about birth options. Objective The aim of this study is to examine the perceptions of women who had cesarean section regarding the concept of “cesarean birth” and “Vaginal birth after cesarean section” with metaphor analysis. Materials and Methods: This study is a qualitative research based on the philosophy of Husserl’s phenomenology, which was carried out between June and November 2022. Within the scope of the research, 50 women who had a cesarean section were interviewed face to face. The metaphor form prepared in line with the international literature was used to determine women’s perceptions of the concept of “Cesarean section” and “Vaginal birth after cesarean section”. Results 25 metaphors for cesarean birth and 28 metaphors for vaginal birth after caesarean section were identified. Considering the common features and analogy aspects of the metaphors obtained, three themes were determined within the scope of cesarean section and vaginal birth after caesarean section. Conclusions This study took a unique approach to revealing women’s birth experiences and perceptions. Vaginal birth after caesarean section is a very valuable birth method for women who have had a cesarean section and are curious about the feeling of vaginal birth. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 418-428